1995
DOI: 10.1126/science.7886456
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Mouse Model of Helicobacter pylori Infection that Mimics Human Disease

Abstract: The human pathogen Helicobacter pylori is associated with gastritis, peptic ulcer disease, and gastric cancer. The pathogenesis of H. pylori infection in vivo was studied by adapting fresh clinical isolates of bacteria to colonize the stomachs of mice. A gastric pathology resembling human disease was observed in infections with cytotoxin-producing strains but not with noncytotoxic strains. Oral immunization with purified H. pylori antigens protected mice from bacterial infection. This mouse model will allow th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
370
2
5

Year Published

1997
1997
2007
2007

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 554 publications
(394 citation statements)
references
References 21 publications
17
370
2
5
Order By: Relevance
“…VacA is a candidate antigen because immunization with VacA confers protective immunity in a mouse model of H. pylori infection (52,53). We show here that two VacA surfaces are strictly conserved among all surveyed m1 and m2 sequences and propose that these surfaces are under selective pressure to be preserved to mediate receptor-binding and oligomerization functions.…”
Section: Sequence Variation Among Vaca Proteinsmentioning
confidence: 84%
“…VacA is a candidate antigen because immunization with VacA confers protective immunity in a mouse model of H. pylori infection (52,53). We show here that two VacA surfaces are strictly conserved among all surveyed m1 and m2 sequences and propose that these surfaces are under selective pressure to be preserved to mediate receptor-binding and oligomerization functions.…”
Section: Sequence Variation Among Vaca Proteinsmentioning
confidence: 84%
“…102 I strains promote gastric damage similar to that observed in humans. 71,104 To date, studies have shown that CagA is one of the proteins produced by the pathogenicity island (cag PAI). Recent studies using isogenic mutants strains lacking the cagA gene have shown that IL-8 induction may not be directly due to CagA protein but to the products of cag PAI genes.…”
Section: Relevance Of Strain Types Of H Pylori In the Outcome Of Infmentioning
confidence: 99%
“…104,127 These models have permitted the testing of prophylactic and therapeutic vaccines containing different antigens, including whole inactivated cells, 1 bacterial lysates, 128 and several purified antigens. To date, researchers have identified several H. pylori antigens which confer protection against H. pylori infection or in eradicating an already established infection in the murine models, including purified VacA, 104 urease (and its subunits), 129 CagA, 130 heat shock proteins (HspA and HspB), 1 and catalase. 131 Therapeutic vaccination has also been successful in ferrets and Rhesus monkeys infected with Helicobacter mustelae and H. pylori, respectively.…”
Section: Vaccination Development For Clinical Use and Future Of The Hmentioning
confidence: 99%
“…SPM326, a type I (CagA ϩ VacA ϩ ) H. pylori strain obtained from a human isolate and adapted to the mouse as previously described (21), was used to infect the dogs. Bacteria were grown and harvested as previously described (8) with minor modifications.…”
Section: Methodsmentioning
confidence: 99%